ANALISIS KINERJA STRUKTUR GEDUNG BERTINGKAT DENGAN METODE RESPON SPECTRUM DITINJAU PADA DRIFT DAN DISPLACEMENT MENGGUNAKAN SOFTWARE ETABS - Ari Mulyo Diah Utami (Jurnal Infrastruktur, 2018)
With so many occurrences of the earthquake in Indonesia, then a lot of the developed analysis- analysis of the earthquake to the structure. Earthquake analysis is divided into two equivalent static earthquake analysis and the analysis of earthquake dynamics. Analysis of dynamical earthquake used to know the performance of high-floor building structures on the lot, irregular, and buildings that require precision. As for the purpose of this research is to analyze the structure dynamical response analysis with a spectrum that is reviewed based on displacement, and drift. In this thesis, the would have discussed building a multilevel structure analysis process shaped Letter L 7-storey method using response spectrum, then analyze his behavior against the burden of life, death and the response spectrum. Reference design using the standard 03-1726-2012 SNI and ATC-40. Conclusion of this research is the result of control performance limits of layan direction X 0, 00403m, and direction Y 0.00400 m already qualified the performance limits of layan .